The RNA helicase DHX34 functions as a scaffold for SMG1-mediated UPF1 phosphorylation - Melero, Roberto (Nat Commun, 2016)
Nonsense-mediated decay (NMD) is a messenger RNA quality-control pathway triggered by SMG1-mediated phosphorylation of the NMD factor UPF1. In recent times, the RNA helicase DHX34 was found to promote mRNP remodelling, leading to activation of NMD. Here we demonstrate the mechanism by which DHX34 functions in concert with SMG1. DHX34 comprises two distinct structural units, a core that binds UPF1 and a protruding carboxy-terminal domain (CTD) that binds the SMG1 kinase, as shown using truncated forms of DHX34 and electron microscopy of the SMG1–DHX34 complex. Truncation of the DHX34 CTD does not affect binding to UPF1; however, it compromises DHX34 binding to SMG1 to affect UPF1 phosphorylation and hence abrogate NMD. Altogether, these data suggest the existence of a complex comprising SMG1, UPF1 and DHX34, with DHX34 functioning as a scaffold for UPF1 and SMG1. This complex promotes UPF1 phosphorylation leading to functional NMD.